Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pada PT Radhika Maritim Indotama Baubau - Nas'ah, Nas'ah; Rafiuddin, Rafiuddin; Kartika, Kartika (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the financial performance of PT.Radhika Maritim Indotama Baubau. In obtaining the desired data the author used two methods, namely the literature study method and documentation, which then used secondary data to complete it. The data used is analyzed quantitatively and qualitatively by analyzing the company’s financial reports, using calculations in the form of financial ratios (liquidity, solvency, and profitability). Based on the results of the research carried out, it was found that the liquidity ratio analysis from 2019 to 2022 was seen from the current ratio and cash ratio was considered not good. From the results of the solvency ratio analysis from 2019 to 2022, the debt to asset ratio and debt to equity ratio is considered not good. From the results of the activity ratio analysis from 2019 to 2022, the Receivable Turn Over and total assets turnover is considered not good. From the results of the profitability ratio analysis from 2019 to 2022, it can be seen that return on total assets and return on total equity are considered not good.